2015
DOI: 10.1039/c5cc01560j
|View full text |Cite
|
Sign up to set email alerts
|

“Decarbonization” of an imino-N-heterocyclic carbene ligand via triple benzyl migration from hafnium

Abstract: An imino-N-heterocyclic carbene underwent three sequential benzyl migrations upon reaction with tetrabenzylhafnium, resulting in complete removal of the carbene carbon from the ligand. The resulting eneamido-amidinato hafnium complex showed alkene polymerization activity comparable to that of a precatalyst containing the intact iminocarbene ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…The representative bond-activation reactions include C−H bond activation on the N substituents, 11−16 dealkylation reactions of N-alkyl NHCs, 17−23 ring expansion and ring opening of the imidazole rings, 23,24 and carbene carbon extrusion. 23,25 Knowledge of these bond-activation reactions has provided valuable insights for reaction mechanism elucidation and new ligand design. 26−30 In addition to these, herein we wish to report a new type of bond-activation reaction of NHCs: namely, dearylation of N-aryl NHCs by low-valent transition metals (Chart 1).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The representative bond-activation reactions include C−H bond activation on the N substituents, 11−16 dealkylation reactions of N-alkyl NHCs, 17−23 ring expansion and ring opening of the imidazole rings, 23,24 and carbene carbon extrusion. 23,25 Knowledge of these bond-activation reactions has provided valuable insights for reaction mechanism elucidation and new ligand design. 26−30 In addition to these, herein we wish to report a new type of bond-activation reaction of NHCs: namely, dearylation of N-aryl NHCs by low-valent transition metals (Chart 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…N-heterocyclic carbene (NHC) ligands have found broad application in catalysis, inorganic synthesis, and materials science. They are heavily used in the stabilization of transition-metal complexes and main-group-element compounds having unusual coordination geometries and oxidation states. In catalysis, NHCs are well-known in the role of enhancing the catalytic performance of transition-metal-catalyzed reactions. , While NHCs in reactions are usually present as spectator ligands, a number of studies have shown that bond-activation reactions on NHC ligands can occur. The representative bond-activation reactions include C–H bond activation on the N substituents, dealkylation reactions of N-alkyl NHCs, ring expansion and ring opening of the imidazole rings, , and carbene carbon extrusion. , Knowledge of these bond-activation reactions has provided valuable insights for reaction mechanism elucidation and new ligand design. In addition to these, herein we wish to report a new type of bond-activation reaction of NHCs: namely, dearylation of N-aryl NHCs by low-valent transition metals (Chart ). This NHC degradation mode was observed in reduction reactions of NHC-cobalt/rhodium-alkene complexes with KC 8 and crown ethers, leading to the conversion of N-aryl NHC ligands into imidazolate and aryl ligands, which differs from Tobisu’s iridium-mediated dearylation reactions of N-aryl NHCs that have dealkylation of the N-aryl group as a key step .…”
Section: Introductionmentioning
confidence: 99%
“…Still, rare examples of substrate activations across metal-NHC bonds have been reported. [5][6][7][8][9][10][11][12][13][14][15][16] In particular, P. Arnold and coworkers have described unique addition/elimination reactions of polar substrates across the metal-carbene bond in a variety of rare-earth and actinide NHC complexes. [11][12][13] In these reactions, the Lewis acidity of the metal and the Lewis basicity of the NHC ligand are not mutually neutralized by the formation of a Lewis acid-base adduct.…”
mentioning
confidence: 99%
“…Skeletal rearrangements of coordinated imidazol(in)-2ylidenes are rare but not unprecedented. Heterocycle ringopening reactions may be preceded by migratory insertion of alkyl co-ligands to the C NHC (Ni), [14] (Hf), [15] or not; [16] imidazol(in)-2-ylidene ring expansion to 6-membered metallacycles can take place via metal insertion into the CÀNbond (Ni, [17] Ru [18] ). Ring expansions involving insertion of heteroelements have been described and recently reviewed; [19] remote lithiation preceding SIMes ring opening has recently been reported.…”
mentioning
confidence: 99%